Analisis Pengaruh Pertumbuhan Ekonomi Dan Pendidikan Terhadap Tingkat Partisipasi Angkatan Kerja Di Kabupaten Pakpak Bharat: indonesia - Safuridar; Rinaldi Syahputra; Fithri Angelia Permana; Furqan; Berutu, ALsantriyani (Jurnal Sociohumaniora Kodepena (JSK), 2022)
This study aims to analyze economic growth and education on the level of labor force participation in Pakpak Bharat Regency. The data analysis method used in this research is quantitative method or time series data. The analytical tool used is Multiple Linear Regression analysis using data from the Central Bureau of Statistics of Pakpak Bharat Regency for 14 years (2008-2021.Based on the results of the study, the equation TPAK = 70.59686 +1.742869 Economic Growth + 3.009641 Education, the equation results show that economic growth and education has a positive effect on the Labor Force Participation Rate in Pakpak Bharat Regency. The results of the t-test on the Economic Growth variable were obtained at 0.2214 > = 0.05 and had no effect on the labor force participation rate and was rejected. In the education variable obtained by 0.8385 > = 0.05 and has an effect on the level of labor force participation and is accepted. The result of the F test is 0.316326 < = 0.05. So it can be stated simultaneously that economic growth and education have no significant effect on the level of labor force participation in Pakpak Bharat Regency, accepted. The results of the coefficient of determination (R2) in this study were obtained at 0.4133 or 41.33%, meaning that the variables of economic growth and education affect the labor force participation rate in Pakpak Bharat Regency by 41.33%, while the remaining 58.67% is influenced by the variable others that were not investigated in this study.